Metschnikowia pulcherrima Influences the Expression of Genes Involved in PDH Bypass and Glyceropyruvic Fermentation in Saccharomyces cerevisiae - Sadoudi, Mohand; Rousseaux, Sandrine; David, Vanessa; Alexandre, Hervé; Tourdot-Maréchal, Raphaëlle (Frontiers in Microbiology, 2017)
Previous studies reported that the use of Metschnikowia pulcherrima in sequential culture fermentation with Saccharomyces cerevisiae mainly induced a reduction of volatile acidity in wine. The impact of the presence of this yeast on the metabolic pathway involved in pyruvate dehydrogenase (PDH) bypass and glycerol production in S. cerevisiae has never been investigated. In this work, we compared acetic acid and glycerol production kinetics between pure S. cerevisiae culture and its sequential culture with M. pulcherrima during alcoholic fermentation. In parallel, the expression levels of the principal genes involved in PDH bypass and glyceropyruvic fermentation in S. cerevisiae were investigated. A sequential culture of M. pulcherrima/S. cerevisiae at an inoculation ratio of 10:1 produced 40% less acetic acid than pure S. cerevisiae culture and led to the enhancement of glycerol content (12% higher). High expression levels of pyruvate decarboxylase PDC1 and PDC5, acetaldehyde dehydrogenase ALD6, alcohol dehydrogenase ADH1 and glycerol 3-phosphate dehydrogenase PDC1 genes during the three first days of fermentation in sequential culture conditions are highlighted. Despite the complexity of correlating gene expression levels to acetic acid formation kinetics, we demonstrate that the acetic acid production pathway is altered by sequential culture conditions. Moreover, we show for the first time that the entire acetic acid and glycerol metabolic pathway can be modulated in S. cerevisiae by the presence of M. pulcherrima at the beginning of fermentation.